2016
DOI: 10.1103/physreva.94.022502
|View full text |Cite
|
Sign up to set email alerts
|

Weighted difference ofgfactors of light Li-like and H-like ions for an improved determination of the fine-structure constant

Abstract: A weighted difference of the g-factors of the Li-and H-like ion of the same element is studied and optimized in order to maximize the cancellation of nuclear effects. To this end, a detailed theoretical investigation is performed for the finite nuclear size correction to the one-electron g-factor, the one-and two-photon exchange effects, and the QED effects. The coefficients of the Zα expansion of these corrections are determined, which allows us to set up the optimal definition of the weighted difference. It … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The extension of experiments to the heaviest ions, including Pb 81+ and U 91+ , is expected in the forthcoming years by the use of the ALPHATRAP Penning-trap setup [22] and the HITRAP facility [23,24]. Measurements with these systems are anticipated to provide an alternative determination of the value of α [25][26][27]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extension of experiments to the heaviest ions, including Pb 81+ and U 91+ , is expected in the forthcoming years by the use of the ALPHATRAP Penning-trap setup [22] and the HITRAP facility [23,24]. Measurements with these systems are anticipated to provide an alternative determination of the value of α [25][26][27]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [26,27] a specific difference of the g factors of low-Z H-and Li-like ions was proposed, for which an even stronger suppression of nuclear effects and their uncertainties can be achieved, leading to an accuracy competitive with the current value of α. A calculation of the nuclear polarization effect extended to Li-and B-like ions showed that these terms can also be largely suppressed in a specific difference of the g factors for two different charge states of the same element [28].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [28], the most accurate at that time theoretical g-factor value for 28 Si 11+ was obtained, g th,2019 = 2.000 889 894 4 (34), and it was found to be 1.7σ away from the experimental value, g exp,2019 = 2.000 889 888 45 (14), presented ibid. The improvement was achieved mainly due to the accurate treatment of the higherorder effects within the perturbation theory.…”
mentioning
confidence: 95%
“…For example, the measurement of the g-factor isotope shift with Li-like calcium ions [27] has opened a possibility to test the relativistic nuclear recoil theory in the presence of magnetic field and paved the way to probe boundstate QED effects beyond the Furry picture in the strong-field regime [30,31]. The high-precision bound-electron g-factor experiments combined with theoretical studies are expected to provide an independent determination of the fine structure constant α [32][33][34]. Moreover, one can search for the effects beyond the Standard Model [35].…”
mentioning
confidence: 99%
“…A relatively direct method consists in comparing the best available theoretical and experimental results, the largest difference between which allowed by the uncertainties, provides a bound for the NP contribution to the g factor. With this method, we also use data on weighted differences of g factors of ions in different charge states [28][29][30][31]. Another method is centered on the isotope shift.…”
mentioning
confidence: 99%